Performance of Purunã beef cows subjected to different nursing managements - Moura, Ivan César Furmann; Kuss, Fernando; Moletta, José Luis; de Menezes, Luis Fernando Glazenapp; Henrique, Douglas Sampaio; Lipinski, Leandro Cavalcante; Martins, Adriana de Souza (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the weight and reproductive performance of beef cows subjected to different nursing managements. During the breeding season of 85 days, 161 beef cows of the Purunã breed were evaluated, according to the following feeding managements: early weaning, cows separated from their calves at 75 days postpartum; controlled nursing, cows separated from their calves at 75 days of age, but taken to nurse once a day during the breeding season; and conventional weaning, cows kept with their calves until the end of the breeding season, at 160 days of age of calves, in average. Fertility rates were not significantly affected by weaning managements, being 97% for early weaning, 96% for controlled nursing, and 90% for conventional weaning. However, early weaning resulted in lower reproductive efficiency (28.26 kg), when compared to controlled nursing (35.09 kg) and conventional weaning (35.34 kg). Beef cows maintained in good body conditions at birth and at the beginning of the breeding season have a high fertility rate, regardless of calf‑feeding management.